Ensino e aprendizagem de expressões algébricas através da exploração, resolução e proposição de problemas - Silva, Renata Ranielly Cabral da (2020)
Teaching and Learning Algebra is a challenge for teachers and students, because it is common to observe in our classrooms the dissatisfaction of students who cannot understand the contents related to Algebra, as well as there are many concerns on the part of teachers who often do not have an adequate methodology that favors algebraic teaching and learning. Through this, this research seeks to identify and analyze which contributions the Methodology Problem Exploration, Solving and Posing can provide to the teaching and learning of algebraic expressions in a way that becomes more comprehensive to the student. The investigation was carried out with students from the 8th grade of an elementary school at a state public school in the town of Ingá - PB. They were chosen because they are students of the teacher / researcher and for observing in the literature that, in this school year, students have greater difficulty in relation to the contents of Algebra. The research is characterized as qualitative (ANDRÉ, 1995; BOGDAN; BIKLEN, 1994), in the pedagogical research modality, defended by Lankshear and Knobel (2008, p. 14). For data collection, we plan and use activities for teaching algebraic expressions that meet the recommendations of the National Curriculum Parameters (1998), from the National Common Curricular Base (2017) and from the authors Friedlander & Arcavi (2017), based on the Problem Resolution Methodology, from the perspective of Problem Exploration, proposed by Andrade, S. (1998, 2017). The data were collected based on the analysis of the students' productions, as well as the notes taken by the teacher / researcher during the activities. Through them, we see the potential of the Exploration, Solving and Posing Methodology for teaching and learning Algebraic Expressions, since it was notorious the active participation of students during the exploration of problems, which started to reflect, argue and justify their ideas , favoring learning with more understanding. Thus, we conclude that the teaching and learning of Algebraic Expressions, through the Methodology Problem Exploration, Solving and Posing, became more comprehensive to the student.